2015
DOI: 10.5194/bg-12-4209-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seawater carbonate chemistry on the calcification of marine bivalves

Abstract: Abstract. Bivalve calcification, particularly of the early larval stages, is highly sensitive to the change in ocean carbonate chemistry resulting from atmospheric CO2 uptake. Earlier studies suggested that declining seawater [CO32−] and thereby lowered carbonate saturation affect shell production. However, disturbances of physiological processes such as acid-base regulation by adverse seawater pCO2 and pH can affect calcification in a secondary fashion. In order to determine the exact carbonate system compone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 80 publications
9
72
0
Order By: Relevance
“…This optimumcurve response pattern was explained by the interaction between HCO − 3 and protons (H + ), where HCO − 3 stimulates calcification as substrate and H + functions as inhibitor (Bach et al, 2011(Bach et al, , 2013. Similar conclusions have also been made in studies with bivalves (Thomsen et al, 2015) and corals (Jury et al, 2010), where it has been noted that the calcification response to changing carbonate chemistry could be the result of the opposing effects of and [H + ]. Jokiel (2011aJokiel ( , b, 2013 Jokiel, 2013;Jokiel et al, 2014).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This optimumcurve response pattern was explained by the interaction between HCO − 3 and protons (H + ), where HCO − 3 stimulates calcification as substrate and H + functions as inhibitor (Bach et al, 2011(Bach et al, , 2013. Similar conclusions have also been made in studies with bivalves (Thomsen et al, 2015) and corals (Jury et al, 2010), where it has been noted that the calcification response to changing carbonate chemistry could be the result of the opposing effects of and [H + ]. Jokiel (2011aJokiel ( , b, 2013 Jokiel, 2013;Jokiel et al, 2014).…”
Section: Introductionsupporting
confidence: 59%
“…A variety of studies highlighted that carbonate chemistry controls calcification through the balance of stimulation by an inorganic carbon substrate (HCO − 3 or DIC) and inhibition by protons (e.g., Bach et al, 2011;Jokiel 2011a;Thomsen et al, 2015). Other studies found that [CO 2− 3 ] or CaCO 3 are the carbonate-chemistry parameters which best predict calcification (e.g., Schneider and Erez, 2006;de Putron et al, 2011;Gazeau et al, 2011;Waldbusser et al, 2014) (9) and (12) Jokiel, 2011aJokiel, , b, 2013Jokiel et al, 2014), which are arguably the physiologically more meaningful parameters to correlate gross calcification with (Bach et al, 2013;Jokiel, 2013;Thomsen et al, 2015;Sects.…”
Section: T Bach: Reconsidering the Role Of Carbonate Ion Concentrmentioning
confidence: 99%
“…While pH is a fundamental property of the carbonate system, OA can also affect organism performance through p CO 2 , HCO 3 − , and/or CO 3 2– dependent pathways 2527 . In the CCLME, aragonite saturation state ( Ω arag ) has emerged as a highly predictive parameter for linking carbonate chemistry change to biological impacts in a number of important taxa 5, 27, 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This condition is often described as "corrosive" (e.g., Feely et al, 2010). Recent laboratory studies indicate that impacts on sensitive species can occur at higher aragonite saturation states as organisms expend additional energy during early life stages (e.g., Thomsen et al, 2015;Waldbusser et al, 2015b). In general, surface waters of the open ocean are typically super-saturated with respect to aragonite (Ω arag > 1; e.g., Feely et al, 2009).…”
Section: Introductionmentioning
confidence: 99%